SADNESS AMONG ADOLESCENTS IN DIFFERENT SOCIAL SETTINGS IN INDONESIA: AN INDIGENOUS PSYCHOLOGY STUDY - Dewi Anjarsari, Novita; Abdul Hakim, Moh.; W. Yuniarti, Kwartarini (HUMANITAS (Jurnal Psikologi Indonesia), 2010)
Adolescence is a transition period filled with a state of storm and stress. These conditions contribute in increasing the level of adolescents´ unhappiness. Each adolescent has a different meaning of sadness depending on their belief. The previous studies stated that Indonesian had positive attitudes towards sad moments. The aim of this research was to discover the meaning of unhappiness among adolescents raised in large cities, rural and urban areas. A total of 426 senior high school students between 1417 years old (urban=151, rural=215, metropolitan=60), were asked to complete open-ended questionnaires by answering the question "What is the meaning behind the sad moments that you describe?" The data was categorized, and then analyzed descriptively. The result shows that 54.2% of the respondents (56.3% of urban, 52.6% of rural, and 55.0% of large city) view unhappy moments as a learning process to maturity. There was no significant difference among adolescents indifferent social settings. This finding demonstrated that Indonesian adolescents cope the sad moments by self-reflections and attempt to adjust themselves towards unpleasant situations.